Pengaruh Observasi Lapangan Dalam Membangun Minat Bisnis Keluarga - Wahyunnisa Aisy Agustini; Rusnandari Retno Cahyan (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
This research aims to investigate the influence of field observations in building interest in family business through literature study research methods. Family businesses are a central pillar of the economy in many countries, and the interest and involvement of family members plays a crucial role in the continuity and growth of these businesses. Field observations, which include family members' direct experience in various aspects of the family business, are thought to have a significant influence in the formation of family business interests. The literature study research method was used to investigate previous studies relevant to this topic. Although there is no research that specifically examines the influence of field observations in building interest in family business, this literature review will present concepts and theories that can provide an understanding of the potential influence of field observations and their practical implications. The results of the literature review show that field observations have the potential to increase the understanding, skills and involvement of family members in the family business. Through direct experience in various aspects of the business, family members can gain a deeper understanding of the dynamics of the family business and increase their intrinsic motivation to be involved in the business.